Review of Implementation Fidelity on Home-Based Virtual and Robotic Rehabilitation Study for Stroke - Soo-Kyung Bok, Youngshin Song, Bohyun Kim, Ancho Lim, Hyunsuk Choi, Hyunkyung Shin, Subeen Ji, Sohyun Jin, (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Background/Objectives: Stroke is a critical chronic health problem in rehabilitation.We aimed to review the fidelityof home-based virtualand robotic rehabilitation studies in stroke survivors. Methods/Statistical analysis: We searched electronic databases such as NBASE, PubMed, Cochrane Library, ProQuest, and CINAHAL to find the relevant literature. Keywords or MeSH terms such as “stroke,” “virtual reality,” “augmented reality,” and “tele* were searched for, and articles published before February 20, 2021, were included. A total of six published articles were reviewed; three studies used virtual therapies for home-based rehabilitation of stroke fighters, and the remaining three used robotic treatment. Findings: In thesix studies selected for review, the FuglMeyer Assessment scale was frequently used to assess physical function. The intervention period, in general, was 20–45 minutes per session for eight weeks, but some studies were unrestricted. Virtual therapy has been shown to vary depending on personal conditions. However, this was like the regular application of 2–3 cycles per week. Intervention doses in robotic therapywere higher than those in virtual treatment. The findings indicate thatvirtual treatment improved upper limb function in all studies, whereas robotic home-based rehabilitation did not improve arm function. Improvements/Applications: The frequency of use and dose of the virtual devicewas lower than those of the robot-assisted device but not inferior to those of the robot. Virtual and robotic devices can be helpful tools for home-based rehabilitation.